Adult Learning and Education Development in Bukovina (1861-1940): A Case Study of the Ukrainian-Speaking Community - Oliinyk, Mariia; Tymchuk, Liudmyla; Fedirchyk, T; Marusynets, M (My University, 2019)
Given the many ways in which adult education, as an important factor of socio-cultural progress and personal growth, has raised a great deal of interest, many studies have given rise to various theoretical approaches to adult education and learning, that still shape research on adult learning at present. Importantly, the social character of literacy is revealed in a variety of ways, since nowadays literacy, in its multi-manifestations, has become a vital set of competencies and practices, interwoven in the fabric of present-day societies. Numerous studies have attempted to explain the prerequisites and preconditions for the emergence of adult learning and education and trace the path of its establishment and further development. The present paper sheds new light on the history of the Bukovinian Ukrainians’ (the Ruthenian population) adult learning and education. There remains a neglected area in the field of adult learning education of other nationalities of Bukovina, so there is still a need for its further investigation. It is worth mentioning that experts have always seen Bukovina as a polyethnic and multiconfessional land, but our focus will revolve around the Ukrainian-speaking adult population’s education, its establishment and development. Traditionally, historical research techniques and approaches can improve the selection of the most appropriate methods to compare data and test theories to forecast the possibilities of their development. Therefore, the holistic understanding of adult education is pivotal to achieving our research goals. Given the results, we found out which factors contributed to the continuation of learning that prevailed in the public education policy and the public sphere of Bukovina from 1861 to 1940. Consequently, within the above-mentioned chronological framework, we have classified the process of adult learning and education development in Bukovina into 5 distinct periods. Such findings pointed to significant gains from the participation in adult education classes in a set of well-established and widely spread reading clubs that have become the first adult learning and education centres. Their activities were aimed at facilitating people’s perception of reality, in order to actively and consciously evaluate the ongoing processes in the society, varying from civic engagement and social cohesion to stimulation of their civil stance and the sentiment of national unity. Analyses of literacy practices and the social contexts in which they were embedded emphasized the enhanced adult learners’ participation and their final successful outcomes. This paper stressed the importance of the Folkuniversitet of Chernivtsi, which was widely recognized beyond the boundaries of both the city and the region. Altogether, the findings of this study reveal a number of important implications for future research.
Keywords: Adult learning; adult education development; re-training; literacy courses; Reading clubs; lectures; instructions; people’s university